2018
DOI: 10.4236/ajps.2018.92023
|View full text |Cite
|
Sign up to set email alerts
|

Development, Validation and Characterization of Genic Microsatellite Markers in <i>Urochloa</i> Species

Abstract: Urochloa (syn. Brachiaria) cultivars represent 85% of tropical pastures occupying 114 million hectares of cultivated grasslands in Brazil. Despite the commercial importance of the Urochloa species, low molecular information is available and is far from saturating the genome. Investigating and obtaining more markers associated to characteristics of difficult and late expression can benefit in accelerating breeding programs of more important species. Aiming to increase the number of molecular markers, genic micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…In addition, the analysis showed that U. brizantha , U. decumbens , and U. ruziziensis were genetically closer to each other than to U. humidicola . This finding has also been observed in later studies using SSR markers ( Jungmann et al, 2009a ; Silva et al, 2013 ; Santos et al, 2015a ; Ferreira et al, 2016 ; Triviño et al, 2017 ; Pessoa-Filho et al, 2017 ; Souza et al, 2018 ).…”
Section: Genomic Tools and Resourcessupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the analysis showed that U. brizantha , U. decumbens , and U. ruziziensis were genetically closer to each other than to U. humidicola . This finding has also been observed in later studies using SSR markers ( Jungmann et al, 2009a ; Silva et al, 2013 ; Santos et al, 2015a ; Ferreira et al, 2016 ; Triviño et al, 2017 ; Pessoa-Filho et al, 2017 ; Souza et al, 2018 ).…”
Section: Genomic Tools and Resourcessupporting
confidence: 85%
“…The Embrapa collection has been evaluated in terms of morphological and agronomic characteristics, reproductive mode (apomictic or sexual), cytogenetics, and genetic diversity, this one mainly involving the use of molecular markers. (e.g., Valle and Savidan, 1996 ; Mendes-Bonato et al, 2002a , b ; Boldrini et al, 2006 ; Risso-Pascotto et al, 2006 ; Nielen et al, 2009 ; Ambiel et al, 2010 ; Jungmann et al, 2010 ; Azevedo et al, 2011 ; Boldrini et al, 2011a ; Vigna et al, 2011a ; Garcia et al, 2013 ; Pessoa-Filho et al, 2015 ; Santos et al, 2015a ; de Paula et al, 2017 ; Souza et al, 2018 ; Corrêa et al, 2020 ; Moraes et al, 2021 ). Based on morphological and agronomic traits, U. brizantha exhibited the greatest variation, which reflects the larger number of accessions and the greater inherent genetic variability.…”
Section: Germplasm Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, the number of currently available molecular genetic resources is limited. Previous molecular studies have increased knowledge of U. decumbens genetics, including the development of sets of microsatellite markers (Ferreira et al, 2016; Souza et al, 2018) and the first transcriptome (Salgado et al, 2017) of the species as well as linkage maps from the interspecific progeny of U. decumbens × U. ruziziensis (Worthington et al, 2016). Other studies with molecular markers have analyzed the genetic relationships of this species to other species in the Urochloa genus (Almeida et al, 2011; Pessoa-Filho et al, 2017; Triviño et al, 2017).…”
Section: Introductionmentioning
confidence: 99%